Implementing enterprise risk management : from methods to applications - Lam, James (Wiley finance series., 2017)
Offering valuable insights on solving real-world business problems using enterprise risk management (ERM), this practical guide gives risk professionals a clear understanding of how to implement an enterprise risk management program for every business. - Resumé vydavatel